Hybrid TSR-PSR in nonlinear EH half duplex network: system performance analysis - Phu Tran Tin; Duy-Hung Ha; Tran Thanh Trang (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Nowadays, harvesting energy (EH) from green environmental sources and converting this energy into the electrical energy used in purpose to supply the communication network devices is considered the main research direction. In this research, we investigate the hybrid TSR-PSR Nonlinear Energy Harvesting (EH) Half-duplex (HD) Relaying network in terms of the Success Probability (SP). For this purpose, we derive the integral-form of the system SP. In addition, we use the Monte Carlo simulation for verifying the correctness of the analytical expression. We can see in the research results that all the simulation and analytical values are the same in connection with all primary system parameters.